Self-Control: Kunci Pergaulan Sehat pada Remaja SMP Muhammadiyah 1 Jombang - Alifia Yasinta Hasmy; Nofi Zahrotul Firdaus; Wardatul Mufidah; Samrotul Fitriyah, Rohemah Rohemah; Fellisa Lilia Anggreeni; M. Chafid Dhotus S.; Dhini Islamy Romadloniah; Ayu Raudhatin Nisa; Helen Grasika Dinata A. (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2026)
Adolescence is a transitional stage characterized by significant physical, emotional, and social changes, making adolescents more vulnerable to negative social influences, particularly those arising from peer pressure. A lack of self-control may increase the likelihood of engaging in risky or deviant behaviors that can negatively affect personal development and social well-being. This community service program aimed to improve students' understanding of the importance of self-control in developing healthy and positive social relationships. The program was conducted on June 22, 2026, at SMP Muhammadiyah 1 Jombang and involved 15 students as participants. The intervention was delivered through psychoeducation using lectures, interactive discussions, and opportunities for participants to share their experiences and opinions. Program evaluation employed a One-Group Pretest–Posttest design using questionnaires to measure changes in students' understanding before and after the intervention. The results demonstrated an improvement in students' knowledge of emotional regulation, self-control strategies, and their ability to identify and choose positive peer relationships. These findings indicate that psychoeducation is an effective approach to strengthening adolescents' self-control and is expected to encourage students to avoid risky behaviors while fostering healthier, safer, and more supportive social environments.